Oh captain, my captain! using social network analysis to help coaching staff identify the leadership of a national sports team - Naraine, Michael; Kerwin, Shannon, 1981-; Parent, Milena M. (London : Human Kinetics, Inc., 2016)
This case study explores the issue of team leadership among players who have been selected to play for their national team in an international tournament. After the coaching staff had solidified the roster, a total of 12 (fictional) players were chosen to represent Canada Basketball on the senior women's development team. With some players having known their teammates for only 2 weeks, the coaching staff has asked the team's analytics specialist to gather data regarding the network of players within the team and present potential captains of the team to the coaching staff. Students will take on the role of the analytics specialist and provide the summary of the analysis to the coaching staff. Specifically, using a social network analysis approach, students will use the team's network of players to determine which individual players are involved in the team's leadership structure as captains. The primary objective of this case study is to afford students an opportunity to be acquainted with social network analysis in a sport management setting.
Originally published in Naraine, M., Kerwin, S., & Parent, M. M. (2016). Oh Captain, My Captain! Using social network analysis to help coaching staff identify the leadership of a national sports team. Case Studies in Sport Management, 5(1), 80-84. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social networks -- Case studies; Leadership -- Case studies